2002
DOI: 10.1148/radiol.2243011284
|View full text |Cite
|
Sign up to set email alerts
|

Isoattenuating Pancreatic Adenocarcinoma at Multi–Detector Row CT: Secondary Signs

Abstract: With no visible tumor-pancreas contrast for isoattenuating tumors, indirect signs such as mass effect, atrophic distal parenchyma, and an interrupted duct sign are important indicators for the presence of tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(166 citation statements)
references
References 15 publications
7
153
3
3
Order By: Relevance
“…Discrimination becomes apparent mainly in the late arterial (pancreatic) phase and to a lesser degree in the portal phase of a biphasic helical or multidetector row CT examination ( fi g. 1 , 3 ). It has been reported that about 90% of pancreatic adenocarcinoma display obvious lower attenuated values with a mean tumorpancreas contrast of about 75HU + 35 during the late arterial phase of CT imaging [36] . The remainder 10% of pancreatic adenocarcinomas exhibit a mean tumor-pancreas contrast of only about 9HU + 11, differences which are not visually perceptible, impeding on the CT detection of small lesions [36] .…”
Section: Tumor Detection In Acute Pancreatitismentioning
confidence: 99%
“…Discrimination becomes apparent mainly in the late arterial (pancreatic) phase and to a lesser degree in the portal phase of a biphasic helical or multidetector row CT examination ( fi g. 1 , 3 ). It has been reported that about 90% of pancreatic adenocarcinoma display obvious lower attenuated values with a mean tumorpancreas contrast of about 75HU + 35 during the late arterial phase of CT imaging [36] . The remainder 10% of pancreatic adenocarcinomas exhibit a mean tumor-pancreas contrast of only about 9HU + 11, differences which are not visually perceptible, impeding on the CT detection of small lesions [36] .…”
Section: Tumor Detection In Acute Pancreatitismentioning
confidence: 99%
“…(19) The same is true with the case of BOP-treated hamsters. However the contrast between tumors and parenchyma in hamster pancreas was slightly inferior to that in humans, despite the higher dose of iopamidol than the manufacturer's recommendations for humans.…”
Section: Discussionmentioning
confidence: 69%
“…Ductal stenosis is a secondary sign of pancreatic neoplasms, both adenocarcinoma and neuroendocrine neoplasms (74)(75)(76); however, a ductal stenosis may occur also in patients with chronic pancreatitis or autoimmune pancreatitis and as a late complication of abdominal trauma. In some patients, the differential diagnosis between a neoplastic and a benign cause of ductal stenosis is complicated by the coexistence in benign disease of a focal pancreatic enlargement due to inflammation, granulation tissue or lymphocytes, and plasma cell in a periductal infiltrate.…”
Section: Main Pancreatic Duct Stenosismentioning
confidence: 99%